Trends in AI, data science, and big data (2017) : observations from two communities (O'Reilly Media, 2017)
"In this video, O'Reilly's Chief Data Scientist, Ben Lorica highlights some recent research initiatives and trends in data from both the AI community and the big data/data science world. Topics include: the emergence of deep learning as a general-purpose machine learning technique; strategies for overcoming the main bottlenecks in running successful AI/machine learning projects (i.e., lack of training data and deploying/monitoring models in production); the transition from offline to continuous learning (including reinforcement learning); and the emerging software and hardware infrastructure for AI and machine learning. This is a must-view for every data scientist, data architect/engineer, data/business analyst, and manager or CxO who wants to stay current in the rapidly evolving world of big data, data science, and AI."--Resource description page